Nature Chemical Biology - Sheppard, Terry L.; SpringerLink (Online service) (New York : Nature Publishing Group US : Imprint: Nature Research.)
Nature Chemical Biology is an interdisciplinary journal that publishes the most innovative and important research advances at the interface of chemistry and biology. The journal publishes research from chemists who are applying the principles, language and tools of chemistry to biological systems and from biologists who are interested in understanding biological processes at the molecular level. The scope of the journal covers all areas of contemporary research at the interface of chemistry and biology.
Keywords: Chemistry; Biochemical engineering; Bioorganic chemistry; Biochemistry; Cell biology; Chemistry/Food Science, general; Biochemical Engineering; Biochemistry, general; Cell Biology; Bioorganic Chemistry